Jigsaw in Action: Bridging Collaboration Gaps in Junior High School Classrooms - Ardani, Kania Farah; Lolita, Yuri (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2025)
This study explores the challenges and solutions in implementing the Jigsaw technique to improve reading comprehension among junior high school students through collaborative learning. Using a qualitative descriptive approach, data were collected through classroom observations, teacher interviews, student questionnaires, and field notes. The participants were purposively selected from a class identified as having significant difficulties in reading comprehension. The findings revealed that while the Jigsaw technique encouraged student engagement, motivation, and peer collaboration, its implementation was not without obstacles. Challenges included disparities in student participation, time constraints, uneven role distribution, and external factors such as socioeconomic differences. These issues often influenced students’ readiness and confidence during group activities. To address them, teachers employed strategies such as scaffolding materials, rotational role assignments, the use of multimedia tools, and adaptive pacing. Student feedback also highlighted the importance of pre-teaching key vocabulary, clear role expectations, and supportive group dynamics. The study concludes that the effectiveness of the Jigsaw technique depends on thoughtful instructional design, sensitivity to learner diversity, and continuous teacher reflection. When applied adaptively, it not only enhances reading comprehension but also supports a more inclusive and student-centered learning environment.